2012
DOI: 10.1186/ar4101
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-dependent effect of treadmill running on lubricin metabolism of rat articular cartilage

Abstract: IntroductionWe aimed to understand the changes in cartilage lubricin expression and immunolocalisation in responsed to treadmill running with different intensities in a rat model.MethodsA total of 24 male Wistar rats were randomly assigned into groups of control (CON), low-intensity running (LIR), moderate-intensity running (MIR), and high-intensity running (HIR). Rats in LIR, MIR, and HIR groups were trained for 8 weeks on the treadmill with low, moderate, and high intensity, respectively. After sacrifice, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…The introduction of rhPRG4 into an injured joint may have several positive consequences. Local PRG4 expression is upregulated by physical activity . The combination of compression and shear in vitro has been observed to increase expression of PRG4 by several laboratories .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of rhPRG4 into an injured joint may have several positive consequences. Local PRG4 expression is upregulated by physical activity . The combination of compression and shear in vitro has been observed to increase expression of PRG4 by several laboratories .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Ni et al, revealed the intensity -dependent impact of treadmill running on the lubricin metabolism of articular cartilage in rats (22). In another study, they showed different cartilage responses by changing the running intensity.…”
Section: Discussionmentioning
confidence: 98%
“…Another important limitation is lack of variety in exercise intensity, although, we chose exercise protocol based on earlier study that showed anti-inflammatory/matrix synthesis effects of treadmill exercise in monoiodoacetateinduced arthritis 15 . As articular cartilage responds to mechanical stimuli with dose-dependent manner 7,12,13,44 , investigating multiple intensity level exercise would be worth doing to elucidate whether these manners are confirmed even in cartilagesubchondral bone unit. Nevertheless, exercise protocol used in this study is consistent with previous studies that assessed chondroprotective effects for adult or instability-induced OA model rat knees (12e18 m/min for 30e60 min/day, 3e7 days/ week) 12,13,15,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in human OA clinical trials are likely to be at various stages of the disease when an exercise intervention is initiated 11 . Conversely, exercise is often initiated in pre-clinical animal models shortly after the PTOA process begins 12,13 . Given that there is phasic development of PTOA with early matrix remodeling and transcriptional activity in an experimental PTOA model 14 , the response to intervention for treating PTOA would depend on the timing of the intervention.…”
Section: Introductionmentioning
confidence: 99%